Luteal blood flow measured by Doppler ultrasonography during the first three weeks after artificial insemination in pregnant and non-pregnant Bos indicus dairy cows - Mubbashar HASSAN; Usman ARSHAD; Muhammad BILAL; Abdul SATTAR; Muhammad AVAIS; Heinrich BOLLWEIN; Nasim AHMAD (The Society for Reproduction and Development, 2018)
The objective of this study was to determine if there are differences in luteal size (LS), progesterone (P4), and luteal blood flow (LBF) between pregnant and non-pregnant Bos indicus dairy cows during the first three weeks after insemination, and whether these parameters are related to each other. Lactating cows (n = 13) of mixed parity with a body weight of 430 ± 18 kg (mean ± SD), showing regular estrous cycle were used in the study. All cows were artificially inseminated and were classified as pregnant (embryonic heartbeat on day 30; n = 8) or non-pregnant (inter-estrus interval 17 to 21 days, n = 5). In order to compare the LS and LBF after artificial insemination, B-mode and color Doppler ultrasonography of ovaries were performed on days 4, 5, 6, 7 (first week), 8, 10, 12, 14, (second week), and 16, 17, 18, 19, 20, 21 (third week) in pregnant and non-pregnant cows. Results revealed that the mean LBF was consistently higher (P < 0.05) during days 7 through 21 in pregnant cows than in non-pregnant cows. The mean LS was higher (P < 0.05) on days 6 and 7, and from day 17 onwards, and the mean concentration of P4 was higher (P < 0.05) on days 19, 20, and 21 in pregnant cows. In conclusion, LBF is a more sensitive parameter than LS and P4 for detection of differences in luteal function between pregnant and non-pregnant Bos indicus dairy cows during the first three weeks after AI.